Anastrozole-related acute hepatitis with autoimmune features: a case report - Inno, Alessandro (BioMed Central, 2011)
BACKGROUND: Two cases of acute hepatitis occurring during treatment with anastrozole have previously been reported, but the underlying mechanisms of liver injury are still uncertain. We report the case of anastrozole-related acute hepatitis with some autoimmune features. CASE PRESENTATION: A 70-year-old woman developed acute hepatitis associated with serum antinuclear antibodies during anastrozole treatment; after drug withdrawal, liver function parameters rapidly improved and serum auto-antibodies were no longer detectable. CONCLUSIONS: Anastrozole-induced hepatotoxicity is a very rare event. Drug-drug interactions or metabolically-mediated damage might be involved, with a possible role of individual susceptibility. Our report suggests that an immune-mediated mechanism may also be considered in anastrozole-related liver injury.